The effect of acid rain exposure to the mass and particle size distribution of limestone soils - Rubio, Aimyel R.; Maaño, John Emmanuel V.; Zarco, Mark Albert H. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Limestone is a naturally occurring soft sedimentary rock. When crushed, it may be used as fill material for the base course of roads, particularly in areas where conventional fill materials are not readily available. However, the alkaline nature of limestone soil makes it susceptible to dissolution when exposed to acidic disposition from natural or man-made sources. The objective of the study is to determine the effects of wet deposition exposure, also known as acid rain, to the particles of the limestone soils. Specifically, this study aims to compare the changes in the mass and particle size distribution of the limestone soils after exposure to simulated acid rain over a period of five-days. Furthermore, the study aims to determine the significance of the difference between the changes due to acid rain exposure and to regular water. Effects of acid rain on limestone soils were recreated by using a solution of sulphuric acid and distilled water with pH=4. The experimental set-up consisted of five trials for each time period of exposure for both acid and distilled water cases. Changes in mass and grain size distribution were measured by D50, and percentage mass passing sieve No. 200 were measured after each day. Results show that the mass lost after exposure increases with time for both acid and control set-ups. Furthermore, the results of sieve analysis show that after exposure, there is a migration of particles to smaller sieve sizes, indicating a breakdown of particles. There is also a consistent decrease in the D50, and increase in the percentage of fines smaller than 0.150-mm. While graphs show a greater apparent loss due to acid exposure, there is no statistical significance in the difference between the effects of the two mediums for exposure. However, statistical tests indicate that there is a statistical significance of duration of exposure for both acid and control cases.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Limestone; Acid rain